Diversity of ectoparasites in sheep flocks in São Paulo, Brazil - Madeira, N. G.; Amarante, AFT; Padovani, C. R. (Kluwer Academic Publ, 2000)
The occurrence of ectoparasites in sheep flocks is frequently reported but seldom quantified. Sheep production used to be a predominantly family activity in the state of São Paulo (Brazil), but it began to become a commercial activity in the past decade. Thus, information about the ectoparasites existing in sheep flocks has become necessary. The present data were obtained by means of questionnaires sent to all sheep breeders belonging to the 'Associação Paulista de Criadores de Ovinos' (ASPACO; São Paulo State Association of Sheep Breeders). Response reliability was tested by means of random visits paid to 10.6% of the respondents. Most of the properties (89.5%) reported the presence of one or more ectoparasites. Screw-worm (Cochliomyia hominivorax) was the most frequent ectoparasite (72.5%), followed by bot fly larvae (Dermatobia hominis, 45.0%), ticks (Amblyomma cajennense) and Boophilus microplus, 31.3%) and finally lice (Damalinia ovis, 13.8%). Combined infestations also occurred, the most common one being screw-worm with bot fly larvae (36.0%) followed by bot fly larvae with ticks (13.9%), screw-worm with ticks (9.3%), bot fly larvae with lice (6.9%), and ticks with lice (5.0%). The most common triple combination was screw-worm, bot fly larvae and ticks (12.8%). Breeds raised for meat or wool were attacked by bot fly larvae and ticks more often than other breeds. Lice were only absent from animals of indigenous breeds. The relationships among these ectoparasites are discussed in terms of sheep breeds, flock size, seasonality and the ectoparasitic combinations on the host.
Keywords: Amblyomma; Boophilus; bot fly; Cochliomyia; Damalinia; Dermatobia; lice; prevalence; screw-worm; sheep; ticks